Clinical Presentation and Outcomes of Acute Disseminated Encephalomyelitis in Adults Worldwide: Systematic Review and Meta-Analysis - Li, Kunyi; Li, Maolin; Wen, Lan; Wang, Qiancheng; Ding, Xin; Wang, Jian (Frontiers in Immunology, 2022)
Background Acute disseminated encephalomyelitis (ADEM) is a rare demyelinating disorder that is often misdiagnosed. To improve early diagnosis, we performed a systematic review and meta-analysis of clinical features, outcomes for ADEM in adults. Methods The PubMed, Embase, Web of Science and Cochrane Library databases were searched for studies reporting the clinical features of adults with ADEM between January 1990 and May 2021. A random-effects meta-analysis model was used to pool data on clinical features and functional outcomes. Results Twelve studies examining 437 adults with ADEM met the inclusion criteria. Overall, the clinical features and diagnostic findings observed in more than two-thirds of the patients were white matter lesions [87.1%, 95% confidence interval (CI)=75-95.6], polyfocal onset (80.5%, 95% CI=50.5-98.9) and pyramidal signs (68.7%, 95% CI =40.0-91.9). The mortality rate was 7.8% (95% CI = 3.3–13.5), and the risk of residual deficits was 47.5% (95% CI = 31.8–63.4). Conclusions Adults with ADEM had worse outcomes than children. Clinicians should maintain high clinical suspicion for patients presenting with certain clinical features and diagnostic findings.